ENERGY EFFICIENT BANDWIDTH CONSTRAINED QOS ENABLED MULTIPATH ROUTING FOR MANETs - Sumathi, N.; Selvadoss Thanamani, Antony (International Journal of Computing, 2011)
In mobile adhoc networks, node has a finite and decreasing energy. Energy saving mechanism is important for the efficient operation of the battery powered network. When a node is transmitting a packet, all the neighboring nodes overhear. Overhearing improves routing efficiency but consumes more energy. Overhearing is caused by the fact that when a unicast transmission is carried out in a node’s immediate neighborhood, it does not have any mechanism for not to receive that packet. Energy consumption during overhearing is same as that during reception. Goal of this work is to develop an energy conserving mechanism due to overhearing. To minimize energy, probability method is applied to randomly select number of overhearing nodes. This probability based overhearing is incorporated into log based pipelined ABM (Available Bandwidth Measurement) and integrated with AOMDV routing protocol. This proposed approach is implemented in NS2 simulator. Simulation results are presented to demonstrate the performance metrics such as throughput, packet delivery ratio, end-end latency, routing overhead, energy and bandwidth consumption of the network.